Reinventando identidades: gênero, raça e nação na literatura de A.A.Aidoo - Silva, Meyre Ivone Santana da (2007)
This paper intends to analyse the African female literary expression as a significant contribution to an alteration in the literary scenario of the Anglophone African countries. African female writers works contribute to the process of history rewriting and the reconstruction of female images in the African societies. Ama ata Aidoo is one these women writers that contribute to the development of an african feminist theory. African feminists fight against neocolonial powers and tradional structures that constitute some mountains to women lives